2012
DOI: 10.1002/tesq.19
|View full text |Cite
|
Sign up to set email alerts
|

English as a Transcultural Language in Swedish Policy and Practice

Abstract: The globalization of English in Sweden is examined as it takes shape in educational policy and practice. Following in the tradition of a "new wave" of language policy and planning research that emphasizes connections between policy and how it is interpreted by local stakeholders, this investigation focuses on textual data from Swedish national curricular documents and observational data of preservice English language educators during teacher training. Discourse analysis was conducted in order to illuminate und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 58 publications
3
71
0
2
Order By: Relevance
“…The growing presence of English in teaching (Wächter & Maiworm, 2014) and research publication (Lillis & Curry, 2010) has become a source of concern for many stakeholders. This is particularly true in the Nordic countries , since English has made important inroads in the societies of these countries also outside the academia (Hult, 2012). Increasingly, this seems to be the case also in the Baltic states, although their level of engagement with English in higher education has become apparent only more recently (Wächter & Maiworm, 2014).…”
Section: Theory Data and Methodsmentioning
confidence: 98%
“…The growing presence of English in teaching (Wächter & Maiworm, 2014) and research publication (Lillis & Curry, 2010) has become a source of concern for many stakeholders. This is particularly true in the Nordic countries , since English has made important inroads in the societies of these countries also outside the academia (Hult, 2012). Increasingly, this seems to be the case also in the Baltic states, although their level of engagement with English in higher education has become apparent only more recently (Wächter & Maiworm, 2014).…”
Section: Theory Data and Methodsmentioning
confidence: 98%
“…The natural use of English that teachers describe as distinguishing English from other foreign language subjects suggests, as Hult (2012) found in Sweden, that teachers imagine the English classroom as a space to learn more about content and less about language use as influenced by social norms. While metacultural awareness through reflection on cultural and historical knowledge is evident in what teachers describe, this awareness seems influenced by Norwegian history and the belief that English is owned by the nations who speak it.…”
Section: Strong Cultural But Weak Linguistic Orientationmentioning
confidence: 90%
“…In Sweden, for example, Hult (2010Hult ( , 2012 found that pre-service teachers and their instructor viewed the English classroom not as a space where language was used for functional communication influenced by social norms but instead as a space where these norms were suspended for the purpose of learning. Instead, participants in the study viewed situated and meaningful use of English as occurring in society and distinct from the use of English in school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…standard Swedish), its five national minority languages and the other mother tongues of its immigrants and their descendants, 4 Ö vdalsk lacks any kind of officialisation. It is not mentioned in the Language Act (SFS 2009:600) nor anywhere else in Sweden's unifying legislation on language (see Hult 2012;Salö 2016: 9-11). The same holds for Sweden's other Scandinavian nonstandards-interchangeably labelled 'vernaculars', 'parish vernaculars', '(local) languages', 'genuine dialects' or 'dialects' 5 -which, just as Ö vdalsk, are in use in some of its rural peripheries.…”
Section: A State Vision Of Linguistic Divisionsmentioning
confidence: 99%